Which symptomatic patients merit urgent referral for colonoscopy? A UK general practice perspective - Jiwa, Moyez; Gordon, M.; Skinner, P.; Olujimi Coker, A.; Colwell, B.; Kenny, R.; Shaw, L.; Campbell, M. (Radcliffe Publishing, 2007)
Objectives: To review the assessment of patients as documented in general practitioners' (GPs') referral letters for urgent and routine referrals to colorectal surgeons. Method: We report data for consecutive referrals to colorectal surgeons in South Yorkshire, UK. Data were collected from hospital medical records and referral letters. A questionnaire survey of 150 GPs in the region about the reasons why they use the cancer referral route was separately administered to a wider community of GPs in the locality. Results: Data for 432 referrals over a six-month period were available for analysis. Seventeen percent of patients were referred contrary to national guidelines. Almost 40% of referrals were sent urgently, cancer was diagnosed in only 2.5% of these. Of those cases sent urgently, almost one-third had significant colorectal pathologies compared to just over 11% of patients referred routinely. Of the 101 GPs responding to the survey, one in eight admitted to referring patients on the cancer fast-track referral pathway at least 'sometimes' in order to access an urgent appointment for some other reason. The clinical reasons why one in five patients was referred urgently could not be surmised from the details recorded in the letters. Conclusion: In most cases, GPs appear to recognise colorectal pathology that requires urgent referral. It may be better to prioritise specialist investigations according to clinical presentation of a variety of significant pathologies rather than only on the basis of the clinical features of cancer.